A Multifunctional Thiophene-Based Electrolyte Additive for Lithium Metal Batteries Using High-Voltage LiCoO2 Cathode. Issue 14 (1st January 2019) - Zheng, Yi; Fang, Wei; Zheng, Hao; Su, Yi; Liang, Xin; Chen, Chunhua; Xiang, Hongfa
Abstract : In this work, ethyl 5-amino-4-cyano-3-(2-ethoxycarbonylmethyl) thiophene- 2-carboxylate (TAEC) is proposed as a functional electrolyte additive for lithium metal batteries using high-voltage LiCoO2 cathode. The TAEC molecular contains the –CN, –NH2 and ester groups on the thiophene core, so that it cannot only improve the cathode electrolyte interface (CEI) on the 4.5 V LiCoO2 surface, but also stabilize the solid electrolyte interface on the lithium metal for lithium dendrite suppression. The TAEC-containing electrolyte exhibits the enhanced cycling stability in Li||LiCoO2 batteries in the range of 3.0∼4.5 V, compared to the conventional electrolyte. Especially, the Li||LiCoO2 cell with the 0.3 wt% TAEC-containing electrolyte delivers a high capacity of 162.7 mAh g −1 after 100 cycles with the capacity retention of 85.1%, far superior to that using the conventional electrolyte (51.2 mAh g −1, 27.5%). Interfacial characterizations prove that TAEC can help to form a thin CEI film with reduced interface impedance and suppress the lithium dendrite growth in lithium metal batteries.